PENERAPAN MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE (SSCS) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI ENERGI TERBARUKAN DI KELAS X SMA - Indah Sari, Liyanti; Z, Fakhruddin; Nor, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The educational process is expected to equip students with critical thinking and problem-solving skills, particularly in physics, which requires a deep understanding of concepts. The results of observations conducted at SMAN 3 Pekanbaru indicated that the cognitive learning outcomes of tenth-grade students were still relatively low, with approximately 60% of students scoring below the Minimum Mastery Criterion (MMC) of 70. This study aimed to analyze students' cognitive learning outcomes and to determine whether there was a difference in cognitive learning outcomes between classes implementing the Search, Solve, Create, and Share (SSCS) learning model and those using conventional learning methods on the topic of Renewable Energy in Grade X at SMAN 3 Pekanbaru. This research employed a quantitative approach using a quasi-experimental method with a Posttest-Only Control Group Design. The research sample consisted of two classes with a total of 80 students, divided into an experimental class and a control class. Data were collected through a cognitive learning outcomes test comprising 20 questions and were analyzed using descriptive and inferential statistics. The results showed that the average score of the experimental class was higher, at 86.32, compared to 78.06 in the control class. The parametric hypothesis testing using the Independent Samples t-Test revealed a significant difference in students' cognitive learning outcomes between the class that implemented the SSCS learning model and the control class that received conventional instruction.